1995
DOI: 10.1111/j.1365-2958.1995.mmi_17051001.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐activated expression of a Streptomyces pristinaespiralis multidrug resistance gene (ptr) in various Streptomyces spp. and Escherichia coli

Abstract: A promoter which controls expression of the pristinamycin multidrug resistance gene (ptr) in Streptomyces pristinaspiralis could be induced by physiological stresses in both Streptomyces spp. and Escherichia coli. In S. pristinaspiralis, the ptr promoter (Pptr) was induced by pristinamycin I (PI) or pristinamycin II (PII). Streptomyces lividans was adopted as a convenient heterologous host for studies of Pptr regulation since it has no known pristinamycin biosynthetic genes. Two key regulatory features were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…This growth arrest precedes antibiotic production (28) and can activate antibiotic biosynthetic genes (31,43), antibiotic resistance genes (50), and stress response stimulons (48), as well as arrest of ribosomal protein synthesis (3). In this work, we demonstrate that this growth arrest corresponds to the transition phase from the first vegetative compartmentalized mycelium to the second multinucleated differentiated mycelium, which is the one which produces antibiotics.…”
Section: Discussionmentioning
confidence: 90%
“…This growth arrest precedes antibiotic production (28) and can activate antibiotic biosynthetic genes (31,43), antibiotic resistance genes (50), and stress response stimulons (48), as well as arrest of ribosomal protein synthesis (3). In this work, we demonstrate that this growth arrest corresponds to the transition phase from the first vegetative compartmentalized mycelium to the second multinucleated differentiated mycelium, which is the one which produces antibiotics.…”
Section: Discussionmentioning
confidence: 90%
“…The developmental database recorded changes in a culture radiolabeled at 16 different time points (12,16,20,24,26,28,30,32,36,40,44,48,54,60,66, and 72 h; Fig. 1) (14).…”
Section: Methodsmentioning
confidence: 99%
“…Similar growth kinetics have been observed in liquid cultures of various Streptomyces species. The T phase has been associated with the activation of antibiotic biosynthetic genes (16) and regulatory elements needed for antibiotic-induced expression of a multidrug resistance gene (26), a starvation response indicated by the accumulation of ppGpp (16), and decreases in the rates of synthesis of ribosomal proteins (1). When thermal stress was applied to these cultures at different times during growth, the levels of thermal induction attained were closely related to growth stage, supporting the notion that developmental and thermal induction of this stress stimulon has common control elements (25).…”
mentioning
confidence: 99%
“…Streptomyces species, in particular, have been the object of considerable attention because these gram-positive bacteria are responsible for the production of the majority of commercially important antibiotics. Uncharacterized regulators designated Pip proteins have been proposed to be involved in the regulation of drug transport genes in a range of Streptomyces species (187,188). Isolation of the Pip protein from the genetically well-defined Streptomyces coelicolor indicated that it was a TetR family repressor that regulates the expression of the MFS antiporter Ptr, which confers resistance to the antibiotic pristinamycin I (34).…”
Section: Drug Transporter Expression In Other Pathogens and Antibiotimentioning
confidence: 99%